FATWA DYNAMICS AND DOCTRINAL CONTROVERSIES: THE AHMADIYYA CASE IN INDONESIAN ISLAMIC DISCOURSE - Nuraeni, Ulvah (STAI ALHIKMAH Jakarta, 2024)
AbstractThis article examines the fatwas issued by the Indonesian Ulema Council (MUI) regarding the Ahmadiyah movement in Indonesia. The research is motivated by the issuance of two MUI fatwas, in 1980 and 2005, stating that Ahmadiyah is heretical and outside Islam. The 1980 fatwa specifically issued a fatwa related to Qadiyani, while the 2005 fatwa covered both Qadiyani and Lahore. MUI fatwas are based on Quranic verses, hadith, and decisions of international Islamic bodies. The emergence of these two MUI fatwas illustrates the rejection and intense monitoring of the Ahmadiyah religious movement in Indonesia. Therefore, this study concludes that the factors of the emergence of two fatwas on Ahmadiyah are based on the influence of Rabithah through the Indonesian Da'wah Islamiyah Council (DDII), the recommendation of the Indonesian Ministry of Religious Affairs in 1979 to supervise Ahmadiyah and other deviant religious sects, the government's indecisiveness in dealing with the Qadiyani Ahmadiyah heresy, the emergence of unrest in the community, and the doctrine of Ahmadiyah Lahore which is in fact similar to Qadiyani. This research uses a qualitative approach and descriptive analysis method that relies on literature review.AbstrakArtikel ini mengkaji fatwa-fatwa yang dikeluarkan oleh Majelis Ulama Indonesia (MUI) mengenai gerakan Ahmadiyah di Indonesia. Adanya penelitian ini dilatarbelakangi oleh penetapan dua fatwa MUI , pada tahun 1980 dan 2005, yang menyatakan bahwa Ahmadiyah adalah sesat dan berada di luar Islam. Fatwa tahun 1980 secara khusus mengeluarkan fatwa terkait Qadiyani, sementara fatwa tahun 2005 mencakup paham Qadiyani dan Lahore. Fatwa-fatwa MUI didasarkan pada ayat-ayat Al-Quran, hadis, dan keputusan-keputusan dari badan-badan Islam internasional. Kemunculan dua fatwa MUI ini menggambarkan penolakan dan pengawasan yang cukup intens akan gerakan keagamaan Ahmadiyah di Indonesia. Oleh karena itu, penelitian ini menyimpulkan bahwa faktor kemunculan dua fatwa tentang Ahmadiyah didasarkan pada pengaruh Rabithah melalui Dewan Dakwah Islamiyah Indonesia (DDII), adanya rekomendasi dari Kementerian Agama RI pada tahun 1979 untuk mengawasi aliran Ahmadiyah dan aliran keagamaan yang menyimpang lainnya, ketidaktegasan pemerintah dalam menghadapi aliran sesat Ahmadiyah Qadiyani, munculnya keresahan di masyarakat, dan doktrin Ahmadiyah Lahore yang nyatanya serupa dengan Qadiyani. Penelitian ini menggunakan pendekatan kualitatif dan metode analisis deskriptif yang bertumpu pada kajian pustaka.